Unreal Engine 4 for design visualization : developing stunning interactive visualizations, animations, and renderings - Shannon, Tom (Addison-Wesley, 2017)
The Official, Full-Color Guide to Developing Interactive Visualizations, Animations, and Renderings with Unreal Engine 4 Unreal Engine 4 (UE4) was created to develop video games, but it has gone viral among architecture, science, engineering, and medical visualization communities. UE4's stunning visual quality, cutting-edge toolset, unbeatable price (free!), and unprecedented ease of use redefines the state of the art and has turned the gaming, film, and visualization industries on their heads. Unreal Engine 4 for Design Visualization delivers the knowledge visualization professionals need to leverage UE4's immense power. World-class UE4 expert Tom Shannon introduces Unreal Engine 4's components and technical concepts, mentoring you through the entire process of building outstanding visualization content-all with realistic, carefully documented, step-by-step sample projects. Shannon answers the questions most often asked about UE4 visualization, addressing issues ranging from data import and processing to lighting, advanced materials, and rendering. He reveals important ways in which UE4 works differently from traditional rendering systems, even when it uses similar terminology. Throughout, he writes from the perspective of visualization professionals in architecture, engineering, or science-not gaming. Understand UE4's components and development environment Master UE4's pipeline from source data to delivered application Recognize and adapt to the differences between UE4 and traditional visualization and rendering techniques Achieve staggering realism with UE4's Physically Based Rendering (PBR) Materials, Lighting, and Post-Processing pipelines Create production-ready Materials with the interactive real-time Material Editor Quickly set up projects, import massive datasets, and populate worlds with accurate visualization data Develop bright, warm lighting for architectural visualizations Create pre-rendered animations with Sequencer Use Blueprints Visual Scripting to create complex interactions without writing a single line of code Work with (and around) UE4's limitations and leveraging its advantages to achieve your vision All UE4 project files and 3ds Max source files, plus additional resources and links, are available at the book's companion website.